Engineering psychology and cognitive ergonomics 9th international conference, EPCE 2011, held as part of HCI International 2011, Orlando, FL, USA, July 9-14, 2011. proceedings - International Conference on Engineering Psychology and Cognitive Ergonomics 2011 Orlando, Fla.); Harris, Don.; SpringerLink (Online service). (Berlin, Heidelberg Springer, 2011)
This book constitutes the refereed proceedings of the 9th International Conference on Engineering Psychology and Cognitive Ergonomics, EPCE 2011, held in Orlando, FL, USA, in July 2011, within the framework of the 14th International Conference on Human-Computer Interaction, HCII 2011, together with 11 other thematically similar conferences. The 67 full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical parts on cognitive and psychological aspects of interaction; cognitive aspects of driving; cognition and the Web; cognition and automation; security and safety; and aerospace and military applications.
Electronic reproduction.
Keywords: Human engineering -- Congresses; Engineering design -- Psychological aspects -- Congresses; Work design -- Psychological aspects -- Congresses; User interfaces (Computer systems) -- Design and construction -- Congresses; Cognitive psychology -- Congresses; Electronic books